2006
DOI: 10.1038/ncb1358
|View full text |Cite
|
Sign up to set email alerts
|

Genomic mapping of single-stranded DNA in hydroxyurea-challenged yeasts identifies origins of replication

Abstract: We report a genome-wide analysis of single-stranded DNA formation during DNA replication in wild type and checkpoint-deficient rad53 yeast cells in the presence of hydroxyurea. In wild type cells, ssDNA first appears at a subset of replication origins and later “migrates” bi-directionally, suggesting that ssDNA formation is associated with continuously moving replication forks. In rad53 cells, ssDNA appears at virtually every known origin, but remains there over time, suggesting that replication forks stall. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
337
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(366 citation statements)
references
References 28 publications
(40 reference statements)
22
337
7
Order By: Relevance
“…Rad3 acts upstream of the S-phase checkpoint mutant cds1 (Xu et al, 2006), which was used by Feng et al (2006) in origin mapping experiments. We found that in the absence of the Rad3 dependent S-phase checkpoint, only two additional peaks were identified and only eight origins that generally replicated late in S-phase (79-85 min) out of the 401 origins (2%) were significantly induced (between 0.07 and 0.16 increases in hybridization ratios).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rad3 acts upstream of the S-phase checkpoint mutant cds1 (Xu et al, 2006), which was used by Feng et al (2006) in origin mapping experiments. We found that in the absence of the Rad3 dependent S-phase checkpoint, only two additional peaks were identified and only eight origins that generally replicated late in S-phase (79-85 min) out of the 401 origins (2%) were significantly induced (between 0.07 and 0.16 increases in hybridization ratios).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the possibility that inhibition of late firing origins by the S-phase checkpoint could interfere with origin identification (Feng et al, 2006), the HU experiment was repeated with a checkpoint deficient strain lacking the rad3 gene (Bentley et al, 1996) (Figure 3). Rad3 acts upstream of the S-phase checkpoint mutant cds1 (Xu et al, 2006), which was used by Feng et al (2006) in origin mapping experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, while cis-acting origin of the replication sequence is clearly defined in prokaryotes, it is ambiguous in eukaryotes. For example, a recent whole-genome analysis using HU revealed an S phase checkpoint in budding yeast that suppresses many origins characterized as late (Feng et al 2006;Raveendranathan et al 2006). However, only a few origins fire late during S phase, and the Rad3-dependent S phase checkpoint has little effect on which origins are fired in fission yeast (Hayashi et al 2007;Heichinger et al 2006).…”
Section: Discussionmentioning
confidence: 99%